2021
DOI: 10.1002/clt2.12086
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab for successful chemotherapy desensitisation: What we know so far

Abstract: Background Hypersensitivity reactions induced by chemotherapeutic drugs may influence the course of the oncologic disease by preventing doctors from prescribing first‐line therapy. In order to prevent another hypersensitivity reaction to the culprit chemotherapeutic agent, the physician can decide between two possibilities: premedication or desensitisation protocols. Rapid drug desensitisation showed successful results for most patients, but some of them may develop symptoms. Although omalizumab is not license… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Omalizumab has been administered in allergen immunotherapy, oral food desensitization, venom immunotherapy, and before aspirin desensitization in management of patients with aspirin-exacerbated respiratory disease contributing to prevent reactions [ 123 , 124 , 125 , 126 , 127 , 128 ]. Omalizumab has also been successfully used as adjuvant treatment in desensitization to chemotherapeutic drugs (i.e., carboplatin and oxaliplatin) in those patients experiencing breakthrough IgE-mediated reactions during desensitization protocol [ 129 , 130 , 131 , 132 , 133 , 134 , 135 ]. It has also been used to prevent hypersensitivity reactions to monoclonal antibodies (infliximab and rituximab) during desensitization [ 136 , 137 ].…”
Section: Prevention Of Allergymentioning
confidence: 99%
“…Omalizumab has been administered in allergen immunotherapy, oral food desensitization, venom immunotherapy, and before aspirin desensitization in management of patients with aspirin-exacerbated respiratory disease contributing to prevent reactions [ 123 , 124 , 125 , 126 , 127 , 128 ]. Omalizumab has also been successfully used as adjuvant treatment in desensitization to chemotherapeutic drugs (i.e., carboplatin and oxaliplatin) in those patients experiencing breakthrough IgE-mediated reactions during desensitization protocol [ 129 , 130 , 131 , 132 , 133 , 134 , 135 ]. It has also been used to prevent hypersensitivity reactions to monoclonal antibodies (infliximab and rituximab) during desensitization [ 136 , 137 ].…”
Section: Prevention Of Allergymentioning
confidence: 99%
“…However, the efficacy of omalizumab has also been described in food allergy, in some cases of hymenoptera venom immunotherapy and as a bridge to oral immunotherapies, atopic dermatitis, idiopathic anaphylaxis, and mastocytosis 4 . Previous studies have reported the use of omalizumab for rapid desensitization to chemotherapeutic agents 5 . Here, we describe a patient with steroid‐resistant NS who developed anaphylaxis on the first infusion of rituximab and subsequent type 1 hypersensitivity reactions during desensitization trials with rituximab using 12‐, 16‐, and 20‐step protocols.…”
Section: Step Solution Rate (Ml/hr) Time Per Step Volume Per Step (Ml...mentioning
confidence: 99%
“…4 Previous studies have reported the use of omalizumab for rapid desensitization to chemotherapeutic agents. 5 Here, we describe a patient with steroid-resistant NS who developed anaphylaxis on the first infusion of rituximab and subsequent type 1 hypersensitivity reactions during desensitization trials with rituximab using 12-, 16-, and 20-step protocols.…”
mentioning
confidence: 99%
“…A literature review regarding preventive premedication strategies in the prevention and management of hypersensitivity reactions to chemotherapy revealed that most premedication regimens including antihistamines, H2 antagonists, leukotriene receptor antagonists and corticosteroids have been derived empirically rather than determined through randomized trials [18 ▪▪ ]. Omalizumab, although not licensed as premedication or adjuvant therapy in chemotherapy desensitization protocols, revealed subservience as a premedication in RDD [19 ▪ ]. However, the published data present great heterogeneity between doses together with the interval between omalizumab injections and chemotherapy.…”
Section: Management Of Adverse Drug Reactionsmentioning
confidence: 99%